Three new species of shoot fly, Atherigona spp., from northern Thailand - Kittikhun Moophayak (2018)
Three new species of shoot fly, Atherigona Rondani (subgenus Acritochaeta Grimshaw) (Diptera: Muscidae), are described from northern Thailand, based on morphological characteristics of males. Unique features of A. komi sp. n. include a distinct spiral groove on the dorsal aspect of the fore femur and two dark apical wing spots, whereas A. chiangmaiensis sp. n. is recognized by the presence of one large patch on the apical wing spot, appearing as a large and smaller wave-shaped patch, and no distinct pattern on tergites. A. thailandica sp. n. displays a remarkable dark boomerang-shaped patch along the wing margin and fore femur, with two rows of long hairs on the dorsal surface. Male terminalia are also different in the new species, showing distinctive characteristics. This paper also presents five newly recorded species in Thailand; Atherigona maculigera Stein, Atherigona ovatipennis vietnamensis Shinonaga et Thinh, Atherigona pallidipalpis Malloch, Atherigona seticauda Malloch, and Atherigona setitarsus Shinonaga et Thinh. A key is provided for the adult males of Atherigona recorded in Thailand, all belonging to the subgenus Acritochaeta, except for A. soccata Rondani.